KEHILANGAN MASSA LAPISAN TEMBAGA-NIKEL/TEMBAGA-NIKEL-SILIKON PADA LARUTAN HCl - Siska Titik Dwiyati; Syamsuir; Muhammad Teguh Pangestu (Jurnal Konversi Energi dan Manufaktur, 2022)
The purpose of this study was to determine the effect of variations in the electroplating time of copper-nickel and copper-nickel-silicon on the corrosion rate of low carbon steel. Copper-nickel and copper-nickel-silicon electroplating were carried out for 10, 20, and 30 minutes. Then the corrosion test was carried out using the weight reduction method for 60 minutes, but every 15 minutes the sample was weighed to see the mass lost. The corrosion rate of copper-nickel plating specimens on low carbon steel in a 3.5% HCl corrosive solution at a plating time of 30 minutes has the highest resistance compared to other time variations of copper-nickel specimens, namely the 15th-minute mass loss of 0.0022 grams. , the mass loss of the second 15 minutes (30 minutes) was 0.0014 grams, the mass loss of the third 15 minutes (45 minutes) was 0.0014 grams, and the mass loss of the fourth 15 minutes (60 minutes) was 0.0021 grams. The corrosion rate of copper-nickel-silicon plating specimens on low carbon steel in a 3.5% HCl corrosive solution at a plating time of 20 minutes has the highest resistance compared to other time variations, namely mass loss in the first 15 minutes of 0.0021 grams, mass loss The second 15 minutes (30 minutes) was 0.0008 grams, the mass loss in the third 15 minutes (45 minutes) was 0.0013 grams, and the mass loss for the fourth 15 minutes (60 minutes) was 0.0015 grams.